1994
DOI: 10.1161/01.cir.90.3.1225
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in beta-adrenergic neuroeffector systems in the human heart.

Abstract: Background Aging decreases cardiac 83-adrenergic responsiveness in model systems and in humans in vivo. The purpose of this study was to comprehensively evaluate the age-related changes in the /3-receptor-G protein-adenylyl cyclase complex in nonfailing human hearts.Methods and Results Twenty-six nonfailing explanted human hearts aged 1 to 71 years were obtained from organ donors and subjected to pharmacological investigation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
115
3
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(132 citation statements)
references
References 83 publications
(10 reference statements)
11
115
3
3
Order By: Relevance
“…31,32 However, ADRB2 density has not changed with age in a number of studies on human tissues including heart and lung. [33][34][35] Our results show that age selectively modulates the density of lymphocyte ADRB2 because only haplotype 1 carriers had a significant (48%) age-associated decline in ADRB2 density. When these same data were examined without considering the ADRB2 haplotype (ie, grouping only according to age), there was no age difference in ADRB2 density.…”
Section: Discussionmentioning
confidence: 60%
“…31,32 However, ADRB2 density has not changed with age in a number of studies on human tissues including heart and lung. [33][34][35] Our results show that age selectively modulates the density of lymphocyte ADRB2 because only haplotype 1 carriers had a significant (48%) age-associated decline in ADRB2 density. When these same data were examined without considering the ADRB2 haplotype (ie, grouping only according to age), there was no age difference in ADRB2 density.…”
Section: Discussionmentioning
confidence: 60%
“…It has been suggested that the increase in MABP with age is a normal age-dependent process that may be a compensatory mechanism for loss of arterial compliance (4). Similarly, the decrease in HR is usually attributed to a diminution in the efficacy of ␤-adrenergic stimulation of the heart, which again is normal and an age-dependent process (41,43) The depressed MABP and HR in diabetic rats observed in the present study is in agreement with many other studies in STZ diabetic rats (9,14,18,20,23,31,39,44). Previous studies from our own laboratory have shown lower HR and reduced systolic blood pressure in conscious STZ-induced diabetic rats (44).…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in uptake-1 results in increased noradrenaline concentrations at the receptor site that can further contribute to βAR desensitization and down-regulation. In aging, it is not clear whether the reduced βAR function is due to a decrease in β 1 AR density [as found in ventricular myocardium (43)] or due to a decrease in the catalytic unit of the adenylyl cyclase [as found in atria (44)]; however, both settings finally result in a diminished cyclic AMP formation upon βAR stimulation. In addition, also in the aging human heart, uptake-1 is reduced and the resulting increase in noradrenaline concentration at the receptor site might contribute to βAR desensitization.…”
Section: Changes In β-Adrenoceptor Functionmentioning
confidence: 99%